2018
DOI: 10.1111/jvp.12717
|View full text |Cite
|
Sign up to set email alerts
|

High interindividual variability in plasma clopidogrel active metabolite concentrations in healthy cats is associated with sex and cytochrome P450 2C genetic polymorphism

Abstract: Clopidogrel response variability has been identified in cats. In humans, evidence suggests that variable clopidogrel active metabolite (CAM) generation is the primary explanation for clopidogrel response variability with differences in body weight, sex, and variable metabolism of clopidogrel primarily due to polymorphisms of the gene encoding cytochrome P450 (CYP) 2C19 as some proposed mechanisms. The aim of this study was to evaluate whether variation in CAM concentrations exists in healthy cats and what the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…The proportion of clopidogrel non-responders in this study is also similar to a different population of cats with the genetic predisposition to HCM (11,22,23). Based on a study by Lee et al (23), this pharmacodynamic variability could be explained by nonsynonymous single nucleotide polymorphisms in the feline CYP2C genes, responsible for encoding the cytochrome P isoenzymes for metabolizing clopidogrel to its active metabolite. However, no studies to date have documented the phenotypes of these mutations in cats based on clopidogrel-specific platelet function assays.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The proportion of clopidogrel non-responders in this study is also similar to a different population of cats with the genetic predisposition to HCM (11,22,23). Based on a study by Lee et al (23), this pharmacodynamic variability could be explained by nonsynonymous single nucleotide polymorphisms in the feline CYP2C genes, responsible for encoding the cytochrome P isoenzymes for metabolizing clopidogrel to its active metabolite. However, no studies to date have documented the phenotypes of these mutations in cats based on clopidogrel-specific platelet function assays.…”
Section: Discussionsupporting
confidence: 78%
“…The fact that male cats are nearly twice as likely to be affected by CATE as female cats suggests that gender differences in platelet function may occur in cats (3,26). Another study also found that female cats had higher clopidogrel active metabolite than male cats after a single dose of clopidogrel highlighting the gender differences in cytochrome P450 activity (23). Future studies with a population of cats that reflects the signalment of cats at risk of CATE are needed.…”
Section: Discussionmentioning
confidence: 99%
“…High interindividual variability in clopidogrel plasma levels has been reported, although this was considered mostly secondary to differences in metabolism (Lee et al . ). The results of the FAT CAT trial (Hogan et al.…”
Section: Abnormalities Of Platelet Function Resulting In Haemorrhagementioning
confidence: 97%
“…There is no published prevalence of drug resistance in cats. High interindividual variability in clopidogrel plasma levels has been reported, although this was considered mostly secondary to differences in metabolism (Lee et al 2019). The results of the FAT CAT trial (Hogan et al 2015) did suggest that clopidogrel is superior to aspirin in reducing the risk of recurrent aortic thromboembolism.…”
Section: Monoclonal Gammopathymentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23] In cats, non-synonymous single nucleotide polymorphisms (SNPs) in the P2RY1 and P2RY12 genes and in the feline CYP2C gene (CYP2C41) were recently reported. 24,25 One study also reported that one of the variants in the feline CYP2C41 gene, CYP2C41:H231R, was associated with increased clopidogrel active metabolite (CAM) concentration after administration of a single dose of clopidogrel in healthy cats. This nding supports the contention that these SNPs could lead to clopidogrel resistance in cats.…”
Section: Introductionmentioning
confidence: 99%